Pelatihan Aplikasi Pelayanan Desa Untuk Penerapan Smart Village Di Desa Sumber Jaya Kecamatan Tambun Selatan - Fathurrozi, Ahmad; Pamungkas, R Wisnu Prio; Kustanto, Prio; Habibi, Ahmad; Aziz, Fawwaz (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Sumber Jaya Village, located in South Tambun District, Bekasi Regency, West Java, has an area of 636 hectares and is surrounded by several other villages. In 2022, the population reached 9,063 inhabitants. Despite its size, the village faces challenges in the development of information technology, where most of the information dissemination is still done manually and most of the village's potential has not been made public. This has resulted in difficulties for local people in accessing information from the village government and in conveying their suggestions and aspirations. The main problems in Sumber Jaya Village include the difficulty of accessing information and complaints, as well as the manual process of handling certificates from village officials. To overcome these problems, the Community Service Program (PKM) aims to implement the smart village concept with proposed solutions including application development and providing training to the community. PKM is arranged in three years.